1997
DOI: 10.1149/1.1837593
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Behavior of Internal Mobilities for Ag(I) and Tl(I) Ions in Molten Nitrates

Abstract: The data on internal cation mobilities, it, in the molten binary nitrate systems (Ag, M)N03 and (Ti, M)N03 (M = alkali metal ion) previously obtained by us have been re-examined. In binary alkali nitrates it is known to be well expressed by an empirical equation u = {A/(Vm -17)} exp (-E/RT), where V,,, is the molar volume; while A, V6, and E are constants nearly independent of the cations with which they are mixed. It is found that in melts containing U for the M deviates negatively from this equation, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A highly-fluorinated cobalt phthalocyanine, 1,2,3,4, 8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro cobalt phthalocyanine, is commercially available (Aldrich Co.). However, it is poorly soluble in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A highly-fluorinated cobalt phthalocyanine, 1,2,3,4, 8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro cobalt phthalocyanine, is commercially available (Aldrich Co.). However, it is poorly soluble in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…It had been reported that metal-containing compounds located in the hydrophilic domains of the Nafion membrane significantly decrease the proton conductivity. [10,11] In our previous paper, [6] we utilized a hydrophobic cobaltporphyrin to be localized in the hydrophobic perfluoroethylene-backbone domain of Nafion, and the proton conductivity of the Nafion membrane was not significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous similar experiments of 6 Li enrichment, mentioned above [43], the separation tubes consisted also of two tubes with different diameters, heated directly with a Nichrome tape. In one of the two runs, 7 Li was anomalously enriched around the connected part of two tubes (int.…”
Section: Anomalous Distribution Of the LI Isotopes Around The Middle mentioning
confidence: 99%
“…Another type of agitation effect is seen for Tl + ; for example, in (Tl, M)NO 3 (M=alkali ion or Ag + ), Tl + renders u M significantly larger than expected from (2), presumably because of the high polarizability of Tl + [43]. It should be stressed that even if (2) does not hold in some cases, the dynamic dissociation model still holds well at least qualitatively, because this model takes into account the perturbation in terms of the free space effect, the tranquilization effect, and the agitation effect.…”
Section: Introductionmentioning
confidence: 99%